The Scientific Structure of Islamic Religious Education (PAI) - Firdaus, Nehna Puteri; Rajiannor, Muhammad; Husna, Ziyadatul; Noor, Hasni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the need for students to understand the scientific structure of Islamic Religious Education (PAI) within the national curriculum and its relevance to character formation. PAI is understood as a subject that not only transfers religious knowledge but also internalizes Islamic values in daily life. The scientific structure of PAI encompasses four main branches: Aqidah Akhlak (Islamic Creed and Morals), Fiqih (Islamic Jurisprudence), Al-Qur’an Hadith, and Sejarah Kebudayaan Islam (Islamic Cultural History/ICH). These branches are designed in an integrated manner to develop the students' cognitive, affective, and psychomotor aspects. This study employs a qualitative descriptive method with a literature review approach through the analysis of curriculum documents, textbooks, and academic journals. The results show that PAI material in Junior High Schools (SMP/MTs) focuses on the basic introduction to faith, worship, and morals, while in Senior High Schools (SMA/MA), it is directed more toward deepening, critical analysis, and the application of religious values in the context of modern life. These findings affirm that the scientific structure of PAI plays a strategic role in creating a religious generation with noble morals who are capable of facing the dynamics of modern life.